Studi Kasus Perkawinan di Bawah Umur - Rahmatiah, Rahmatiah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
Marriage at an early age is one of the factors increasing the number of divorces, violence in the household, as well as less mature in facing the challenges in the household. Selfishness and rely on the old man's treasure, is also one of the trends in the household who previously was married at a young age. Employees Marriage Registrar, although as a registrar, controller and register every marriage, should also be more careful and firm in carrying out its duties and its role in society, in order to create a family mawaddah and mercy.